Challenging the Mainstreams: Broadcasting Salafi Da'wah on Indonesian TV Channels - Subakir, Ahmad (Universitas Islam Negeri Mataram, 2024)
This article examines Salafi da'wah (Islamic proselytizing) movements on private TV stations at the national level. The proliferation of da'wah on private TV in post-Suharto regimes is considered part of the increasing commodification of Islam, which targets middle-class Muslims as a market for economic benefits. The routine appearances of these preachers have shaped alternative religious authority that challenges and competes with the conventional ones from Islamic organizations such as Nahdlatul Ulama or Muhammadiyah and Islamic education institutions such as pesantren or Islamic universities. Since 2010, Salafi da'wah has challenged this by providing da'wah contents that focus on educating Muslims to be more pious. Drawing from participatory observation and in-depth interviews with program producers and other related parties, this article strives to answer how the Salafi da'wah movement attempts to dominate the Islamic public sphere in the country and face competition with other religious authorities through da'wah programs on TV. It is argued that the emergence of the Salafi authority through the da'wah program on TV has challenged the dominance of mainstream da'wah of Nahdlatul Ulama or Muhammadiyah in the Indonesian public sphere.